The Mediating Role of Problematic Alcohol Consumption on the Association Between Pandemic-Related Strains and Domestic Violence Across Six Countries - Leal, Wanda (Journal of interpersonal violence, 2025)
Research has documented that domestic violence increased worldwide during the COVID-19 pandemic. Studies have also suggested that alcohol use, which also increased during COVID-19, is a risk factor for domestic violence victimization. However, research has yet to examine whether alcohol consumption mediated the relationship between pandemic-related stressful events and domestic violence. Using structural equation modeling, the current study examines the impact of three types of pandemic-related strains (financial problems, familial problems, and work problems) on individual assessments about whether their drinking became problematic during the pandemic and then whether problematic alcohol use increases the risk of psychological and physical domestic violence. This model was analyzed across six countries: Ukraine, The Netherlands, Pakistan, Denmark, Guatemala, and the United States. Results indicate that the associations between pandemic-related strains and self-assessed problematic drinking varied by country. However, across all countries, problematic alcohol consumption was associated with increased physical and psychological domestic violence victimization. Overall, the findings of the current study support the use of programs that aim to reduce problematic consumption of alcohol with the hopes that they may, in turn, reduce psychological and physical domestic violence victimization.